Prolonged aerial chase of Willow Grouse Lagopus lagopus by Common Raven Corvus corax - Högstedt, Göran (Ornis Norvegica, 2014)
Two vigorously fighting male Willow Grouse Lagopus lagopus were simultaneously attacked by a Common Raven Corvus corax and a Rough-legged Buzzard Buteo lagopus. The raven pursued one of the grouse over 900 m; the chase ended when the grouse dived into dense willows. The two birds kept the same distance, meaning that the raven flew at roughly 75 km/h (maximum level flight speed of Willow Grouse).